OF RUINS AND SERVEDION: ethnographic approaches to haciendas’s memories of the Zongolica, Veracruz - De Marinis, Natalia (Universidade de Brasília, 2018)
This article presents initial approaches of an ongoing investigation about the memories of haciendas in the Nahua indigenous region of Zongolica, Veracruz. It investigates how the world of haciendas becomes an emblem of political and racialized hierarchies, as well as of the complex interethnic relations that generate violence and spoils on certain subjects so that they are silenced and accepted. Based on ethnographic records and interviews with a variety of actors, it analyzes the ambiguity in which indigenous memories are woven about the haciendas and the way in which they emerge and are silenced in the current context of violence and territorial dispossession.